PENERAPAN MODEL COPERATIVE LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI GERAK DI SMP NEGERI 2 DELIMA - Israfiddin (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2018)
The lower result of students achievements in the last few years were influenced by several factors, among others are the methods used by the teacher which are not appropriate in the teaching and learning process. This research was conducted to know the improvement of learning outcomes. This study used the Quasi Experimental design through The Matching-Only Pretest-Posttest Control Group Design which was done at SMP Negeri 2 Delima. The sample used was a purposive sampling – that was an experimental class treated with a Cooperative learning model and a control class taught by conventional methods. Data collection was done by pretest and posttest to find out the improvement in student learning outcomes. The N-gain test showed the average score of students taught with the CL model has increased by 71% in the excellent category, while the average score of students taught with conventional learning methods has increased by 36% in the category medium